Comparing the Clinical Characteristics, Laboratory Findings, and Outcomes between Epidemic and Episodic Methanol Poisoning Referrals; a Cross-sectional Study - Hadipourzadeh, Mehdi; Ebrahimi, Sara; Ziaeefar, Pardis; Zamani, Nasim; Falahati, Hassan; Roberts, Darren M; Hassanian-Moghaddam, Hossein (Archives of Academic Emergency Medicine, 2021)
Introduction: Due to illegal manufacturing and sales of alcoholic beverages, epidemic outbreaks of methanol poisoning may occur. The aim of this study was to determine if there were differences in the severity, course of poisoning, and outcomes between methanol-poisoned patients admitted during an outbreak versus those who were admitted following episodic exposures. Methods: The present retrospective study was performed in a single referral poisoning center between March 2018 and March 2019 in patients with confirmed methanol poisoning. During this time, in addition to episodic cases of methanol intoxication, there were three methanol poisoning outbreaks. Outbreaks were characterized by an unexpected increase in the number of methanol-poisoned patients in a short period of time, which impacted resources and decision-making. The two groups were compared regarding their severity of poisoning, sessions of hemodialysis, and clinical outcomes. Results: Outbreak cases had a higher level of methanol than episodic cases. Odds of being dialyzed more than once was 5.4 times higher in the cases presenting during an outbreak (95% CI 2.1-14.0; p=0.001). Mean hospital stay, intubation/mechanical ventilation, and death were similar between the two groups. An evaluation of the alcoholic beverage samples available in the Iranian black market during the outbreak showed a 7-percent methanol concentration with no ethanol content. Conclusions: Poisoning risk may be higher during methanol outbreaks due to the higher methanol concentrations, requiring more hemodialysis sessions for persistent metabolic acidosis. In addition to alcohol dehydrogenase blockade, careful risk assessment of all methanol poisonings can assist with stratifying the priority for, and duration of, hemodialysis to optimize outcomes.